Differentiation of Brucella abortus bv. 1, 2, and 4, Brucella melitensis, Brucella ovis, and Brucella suis bv. 1 by PCR. - Bricker, B J (1994)
Several PCR assays which identify the genus Brucella but do not discriminate among species have been reported. We describe a PCR assay that comprises five oligonucleotide primers which can identify selected biovars of four species of Brucella. Individual biovars within a species are not differentiated. The assay can identify three biovars (1, 2, and 4) of B. abortus, all three biovars of B. melitensis, biovar 1 of B. suis, and all B. ovis biovars. These biovars include all of the Brucella species typically isolated from cattle in the United States, a goal of the present research. The assay exploits the polymorphism arising from species-specific localization of the genetic element IS711 in the Brucella chromosome. Identity is determined by the size(s) of the product(s) amplified from primers hybridizing at various distances from the element. The performance of the assay with U.S. field isolates was highly effective. When 107 field isolates were screened by the described method, there was 100% agreement with the identifications made by conventional methods. Six closely related bacteria (Agrobacterium radiobacter, Agrobacterium rhizogenes, Ochrobactrum anthropi, Rhizobium leguminosarum, Rhizobium meliloti, and Rhodospirillum rubrum) and two control bacteria (Bordetella bronchiseptica and Escherichia coli) tested negative by the assay.